Assessment in Emergent Literacy - Pence, Khara L. (Plural Publishing, Inc., 2007)
This practical guide to identifying preschool and early school-aged children's strengths and needs across multiple domains of emergent and early literacy, includes phonological awareness, print awareness, narrative, vocabulary, and motivation. Specific approaches to assessing and monitoring growth in high priority areas of literacy are provided. This handbook also provides guidance for evaluating children's learning environments, including supports with the home and classroom